Predicting the Potential Distribution of Apis Dorsata Using MaxEnt Model in Sundarbans, Bangladesh - Mollah, Tanjinul Hoque; Jony, Md. Raysul Islam; Ferdous, Monalisha; Aunkur, Md. Masuk Mowla; Ibnat, Atia (The Jahangirnagar Review, 2024)
The Sundarbans, the largest single tract of mangrove forest in the world, is famous for its economically and ecologically important flora and fauna. The Sundarbans of Bangladesh is the main natural home of the giant honeybee, Apis dorsata, commonly known as the giant honeybee. However, this iconic pollinator species faces mounting threats. This study aims to predict the potential distribution of Apis dorsata within the Sundarbans region. To fulfil the aim, comprehensive data on climatic variables, relevant environmental factors and chronological distribution of Apis dorsata, were collected and analyzed. Using species distribution modeling techniques, the current and potential habitats of Apis dorsata were mapped. Besides that, potential changes in the species distribution were evaluated using environmental variables such as temperature, rainfall, evapotranspiration, and soil nutrients such as nitrogen, potassium, phosphorus and soil pH. Anthropogenic factors such as deforestation and land use changes were considered in the analysis to account for human-induced effects on the ecosystem. For this study 285 questionnaires, 5 FGDs and 3 KII were conducted randomly with a 95% confidence level and 5% error margin. The result indicates that climatic conditions are likely to exert a considerable influence on the distribution of Apis dorsata in the Sundarbans region. This model predicts a shift in suitable habitat zones, potentially leading to both range expansions and contractions. Besides that, this study emphasizes the urgency of implementing adaptive management strategies to conserve Apis dorsata and its habitat in the face of environmental changes. Conservation efforts should focus on preserving and restoring critical habitats, adopting sustainable land use practices, and mitigating greenhouse gas emissions. Furthermore, engaging local communities in conservation initiatives is essential to ensure the successful protection of this ecologically valuable species and its associated ecosystem services.